A preliminary random checklist of benthic organisms in selected lakes of West Peninsular Malaysia - Chew, Jia Ming; Yap, Chee Kong; Ismail, Mohamad Saupi; Ahmad Wakid, Sarini; Wan Solahudin, Wan Mohd Syazwan; Abd Aziz, Nor Azwady; Mustafa, Muzkhali; Okamura, Hideo; Horie, Yoshifumi; Ong, Meng Chuan; Setyawan, Ahmad Dwi; Yap, Chee Wah; et al. (MedCrave Group, 2023)
The freshwater ecosystem (Kelana Jaya Lake, Seremban Lake Garden and Kanching Eco Forest Park) of west Peninsular Malaysia was the focus of the study’s attempt to offer a current checklist of benthic organisms. Three benthic organisms were identified in the urbanized Kelana Jaya Lake, namely the red-rim melania (Melanoides tuberculata), apple snail (Pomacea sp.), and an Odonata damselfly nymph. Four different species were identified for Seremban Lake Garden: Hydrilla verticillata, Viviparus sp., nymph of Odonata, and Macrobrachium sp. The freshwater prawn Macrobrachium was the only genus identified for Kanching Eco Forest Park. Our attempts to promote aquatic ecosystem management and conservation in Malaysia can use the checklist of benthic creatures from the freshwater ecosystems as a continuous baseline for future reference.